Traumatisms of the duodenum.: treatment - Estrugo, Roberto (Cirugía del Uruguay, 1989)
Author studys two aspects of treatment: intraoperative exploration, and repair procedures. As regards exploration, it must be exhaustive and very thorough with extensive movilization in order to avoid the possibility of not recognizing a duodenal lesion which will certainly evolve to a retro-peritoneal abscess or diffuse peritonitis and eventually death.